Manuscrito del aperreamiento (Manuscript of the Dogging): A "Dogging" and Its Implications for Early Colonial Cholula. - Diel, Lori Boornazian (Ethnohistory)
The Manuscrito del aperreamiento (Manuscript of the Dogging), from Cholula Ca. 1560, presents a graphic image of a dog attacking a bound indigenous priest. Certainly appalling to modern viewers, the work is often seen as an indictment against the Spaniards pictured. In this article, I consider this traditional interpretation and show that it is not entirely satisfactory. Though the Spaniards pictured in the Manuscrito were each accused of cruelties against indigenous peoples, none of these accusations mention the spectacular dogging pictured in the Manuscrito. I then provide a more nuanced reading of the imagery in the Manuscrito and a consideration of its early colonial context and argue that while the work does document a clash of Spaniards versus indigenes, it also establishes a contrast between a Christian indigenous leader and his pagan countrymen. In so doing, the Manuscrito communicates the culpability of the indigenous victims for their harsh punishment. By comparing this image with doggings in other pictorial sources, I show that violent images such as these communicated both the rebellious nature of the indigenous victims and the cruelties of the Spanish conquerors.